Ten‐year mortality trends among persons diagnosed with HIV infection in England and Wales in the era of antiretroviral therapy: AIDS remains a silent killer. Issue 10 (15th May 2013) - Simmons, RD; Ciancio, BC; Kall, MM; Rice, BD; Delpech, VC
<x xml:space="preserve">Abstract</x> Objectives We present national trends in death rates and the proportion of deaths attributable to AIDS in the era of effective antiretroviral therapy (ART), and examine risk factors associated with an AIDS‐related death. Methods Analyses of the national HIV‐infected cohort for England and Wales linked to death records from the Office of National Statistics were performed. Annual all‐cause mortality rates were calculated by age group and sex for the years 1999–2008 and rates for 2008 were compared with death rates in the general population. Risk factors associated with an AIDS‐related death were investigated using a case–control study design. Results The all‐cause mortality rate among persons diagnosed with HIV infection aged 15–59 years fell over the decade: from 217 per 10 000 in 1999 to 82 per 10 000 in 2008, with declines in all age groups and exposure categories except women aged 50–59 years and persons who inject drugs (rate fluctuations in both of these groups were probably a result of small numbers). Compared with the general population (15 per 10 000 in 2008), death rates among persons diagnosed with HIV infection remained high, especially in younger persons (aged 15–29 years) and persons who inject drugs (13 and 20 times higher, respectively). AIDS‐related deaths accounted for 43% of all deaths over the decade (24% in 2008). Late diagnosis (CD4 count < 350 cells/μL) was the most important predictor of dying of AIDS [odds ratio (OR) 10.55; 95% confidence interval (CI) 8.22–13.54]. Sixty per cent of all‐cause mortality and 81% of all AIDS‐related deaths were attributable to late diagnosis. Conclusions Despite substantial declines, death rates among persons diagnosed with HIV infection continue to exceed those of the general population in the ART era. Earlier diagnosis could have prevented 1600 AIDS‐related deaths over the decade. These findings highlight the need to intensify efforts to offer and recommend an HIV test in a wider range of clinical and community settings.